ANALYSIS OF UTILIZATION OF THE REGIONAL MANAGEMENT INFORMATION SYSTEM (SIMDA) IN THE REGIONAL SECRETARIAT OF SOUTH BOLAANG MONGONDOW REGENCY - Abdillah Gonibala; Arifin Tahir; William Mooduto (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This study aims to identify and analyze the constraints and subsequent efforts in utilizing the Regional Financial Management Information System (SIMDA) at the Regional Secretariat of South Bolaang Mongondow Regency. A descriptive qualitative approach was employed, with in-depth interviews as the primary data collection technique. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing/verification. The study reveals several critical constraints: (1) Human Resources: an insufficient number of operators and suboptimal technical proficiency in ensuring data accuracy; (2) Technology: the system has not yet functioned as a fully integrated Management Information System; and (3) Infrastructure: a shortage of computer hardware and the absence of dedicated operator workstations. Efforts to address these issues include strengthening leadership commitment to budget allocation, enhancing human resource capacity through regular technical guidance, and ensuring sustainable funding for system maintenance and management.